2015
DOI: 10.4236/ampc.2015.59037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thickness on Magnetic Dipolar and Exchange Interactions in SmCo/FeCo/SmCo Thin Films

Abstract: SmCo/FeCo/SmCo trilayer was deposited with two different thickness configurations for soft phase (FeCo); 50 nm/10 nm/50 nm and 50 nm/25 nm/50 nm were deposited on Si (111) substrate and Ta (50 nm) seed layer by RF magnetron sputtering in a pressure, p, of 30 -35 m Torr. After deposition the films were annealed under Ar atmosphere at temperature T equal to 923 and 973 for different times followed by quenching in water. X-ray diffraction patterns were obtained to identified phase presents and calculate average c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The results also called by nonhysteresis condition with zero coercivity and retentivity, which indicated that the sample ex-hibits an isotropic characteristic without a preferential axis [27]. Moreover, it indicates that under a normal sintering temperature, the material temperatures of 500 °C and 400 ℃ exhibit ferromagnetic properties with a magnetic saturation of 0.219 and 0.239 emu/g [27][28][29]. In the magnetic nanoparticles, the particle size significantly influences the magnetic strength [18].…”
Section: Resultsmentioning
confidence: 84%
“…The results also called by nonhysteresis condition with zero coercivity and retentivity, which indicated that the sample ex-hibits an isotropic characteristic without a preferential axis [27]. Moreover, it indicates that under a normal sintering temperature, the material temperatures of 500 °C and 400 ℃ exhibit ferromagnetic properties with a magnetic saturation of 0.219 and 0.239 emu/g [27][28][29]. In the magnetic nanoparticles, the particle size significantly influences the magnetic strength [18].…”
Section: Resultsmentioning
confidence: 84%